Woman in the wild : the everywoman's guide to hiking, camping, and backcountry travel - Paul, Susan Joy (Falcon, 2021)
"Few experiences rival a grand outdoor adventure. Hiking into the wilderness, camping under the stars, and exploring the backcountry offer new challenges that awaken a woman's spirit and test her soul. Adventurer and guidebook author Susan Joy Paul provides real instruction for women of all ages and skill levels, from beginners to intermediate hikers and experienced mountaineers. She shares details gleaned from two decades of training and real-world experience, bringing together everything a woman needs to know to be safe, independent, and self-reliant at camp and on the trail"--